DEVELOPMENT OF SOFTWARE AND THERMOECONOMIC ANALYSIS OF COMBINED HEAT POWER SYSTEM - ANTONIUS NUGROHO CAHYADI (NIM : 13104161); Pembimbing Utama : Dr. Ir. I Made Astina
The total of national electricity production in 2008 decreased 4.9% compared to the previous year. This electricity production can not meet the needs of the national electricity. National electricity consumption increases up to 7464 GWh in the same year. Considering this conditions, the charges of an electricity generation with reliable and efficient technology as the center of power source need to be developed well. Combined Heat Power (CHP) system is one solution that can be choosed to overcome the problems. CHP is a system consist of two forms energy generation in the form of electricity and heat simultaneously from a single source of primary energy fuel. This system is different from the conventional system because the heat from the exhaust gas used again for the next power cycle. This CHP system performance will be increased if the component cooling system added to the system. Because of the compressor work is based on volumetric flow, the condition of higher air temperature makes the air mass flow rate decrease. Hence, air temperature entering the compressor need to be cooled so that air mass flow rate will be bigger. Increasing of the air mass flow rate will enhance power generation and increase efficiency of CHP system. Based on thermodynamics evaluation by using the software simulator, more capacity of power generated if cooling system is added to the CHP system. Reviewed aspects of economic, CHP system modelling with additional cooling system is able to generate a large profit. Cooling air from temperature 32 oC to the ISO conditions at 15 oC and RH 60% obtained percentage of net power increase up to 7,8% or net power increase from 149,731 MW up to 161,552 MW , an increase 1.25% of thermal efficiency, with an estimated net profit Rp. 18.4 Billion / year.